Hubungan Antara Peran Pengawas Menelan Obat (PMO) dengan Keberhasilan Pengobatan Tuberkulosis Paru Kategori I - Selly Septi Fandinata; Rizky Darmawan (Journal Syifa Sciences and Clinical Research, 2019)
TB is an infectious disease caused by Gercobacterium tuberculosis that attacks the lungs and can cause disturbances in the respiratory tract. The DOTS Program can help the achievement of successful treatment targets. The role and motivation of PMO and family are essential for the successful treatment of lung TB patients. This type of study is an analytical observational research with prospective data collection in March – May 2019, which is recorded as medical data of patients diagnosed with lung TB category I in September – November 2018 at Rubaru Puskesmas Sumenep Regency. The purpose of this research is to know the role of PMO relationship with the successful treatment of lung TB category I. With the number of samples of this research 40 patients. The results of this study using Pearson correlation statistics indicate that the value significance 0.013 < 0.05, this means a significant link between the PMO role with the success of patient treatment. The value of the correlation coefficient R obtained from 0388, the relationship between PMO role and the success of patient treatment in direct, this means that the greater the role of PMO then the higher the success of treatment, the smaller the PMO role then the lower the Successful treatment. In addition, the table also gained that the relationship between the PMO role and the successful treatment of the patient is weak due to the correlation coefficient of R < 0.4.